OPTIMIZING THE USER EXPERIENCE IN E-LEARNING: THE KEY ROLE OF CROSS-PLATFORM ARCHITECTURE IN CLOUD EDUCATION SYSTEMS (Multidisciplinary Journal of Science and Technology, 2026)
This article investigates the mechanisms for enhancing User Experience (UX) in e-learning systems within the cloud computing environment. The significance of cross-platform architecture in ensuring seamless integration between various technical devices and operating systems is analyzed. Based on the experiences of leading countries such as Finland and South Korea, scientific proposals for creating cross-platform cloud platform architectures for the education system of Uzbekistan are put forward.